Chronic bacterial and parasitic infections and cancer: a review - Vassilis Samaras; Petros I. Rafailidis; Eleni G. Mourtzoukou; George Peppas; Matthew E Falagas (Journal of Infection in Developing Countries)
Background: A relatively underestimated facet of infectious diseases is the association of chronic bacterial and parasitic infections with cancer development. Therefore, we sought to evaluate the evidence regarding the association of such infections with the development of malignancy, excluding the overwhelming evidence of the association of Helicobacter pylori and cancer.